2020
DOI: 10.31235/osf.io/z4ndc
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spreading the disease: The role of culture

Abstract: This paper investigates the “cultural” transmission of the SARS-CoV-2 outbreak.Using West Germany data we observe that in predominantly Catholic regions with stronger social and family ties, the spread and the resulting deaths per capita were much higher compared to non-Catholic ones at the NUTS-3 level. This finding could help explain the rapid spread and high death toll of the virus in some European countries compared to others in the initial stage. Looking at differences within a specific count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Second, intergenerational co-residence may reflect a more widespread presence of active religious communities encouraging physical contacts conducive to the spread of Covid-19. A carefully designed study of 312 areas in Germany with varying proportions of Catholics found that Covid fatalities were higher in areas with higher proportions of Catholics ( Laliotis and Minos, 2020 ). The authors hypothesize that Catholics may have stronger social and family networks, which e.g.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, intergenerational co-residence may reflect a more widespread presence of active religious communities encouraging physical contacts conducive to the spread of Covid-19. A carefully designed study of 312 areas in Germany with varying proportions of Catholics found that Covid fatalities were higher in areas with higher proportions of Catholics ( Laliotis and Minos, 2020 ). The authors hypothesize that Catholics may have stronger social and family networks, which e.g.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Unfortunately, we did not have data on excess mortality for each area in our data set. An example of a study based on excess mortality after Covid limited to a particular country is Laliotis and Minos (2020) .…”
mentioning
confidence: 99%
“…Other economic studies focus on firms' strategies to limit the crisis impact; to date, these studies have underestimated impacts such as mental health (18). Observational or simulation-based studies based on sociology, psychology and economic approaches emphasize the efficiency of measures to change individuals' behavior and modulate outbreak dynamics (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Other economic studies focus on rms' strategies to limit the crisis impact; to date, these studies have underestimated impacts such as mental health (18). Observational or simulation-based studies based on sociology, psychology and economic approaches emphasize the e ciency of measures to change individuals' behaviour and modulate outbreak dynamics (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%